Notice of Coffins (formed of Stone Slabs) found on the Farm of Milton, Haddingtonshire (Proceedings of the Society of Antiquaries of Scotland, 1862)
Having excavated a coffin found at the Burial Knowe on Milton farm by builders, the author and two other members of the Society then excavated two similar cists nearby although only two of the three contained human remains. No other grave goods were found at these sites, leaving the author to speculate on their age by comparing them to similar burial sites in both Scotland and England.